2018
DOI: 10.1016/j.jor.2018.01.043
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive (MIS) Tönnis osteotomy– A technical annotation and review of short term results

Abstract: We have described a minimally invasive Tonnis osteotomy as a viable option based on our results. This technique is recommended for those who are conversant with the traditional pelvicosteotomies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 14 publications
0
10
0
3
Order By: Relevance
“…For the osteotomy position, it is suggested that the osteotomy should be placed as far proximally as possible on the ischial spine to minimize the effect of the rotation angle of the osteotomy site because of the limitation by the sacrospinous ligament. 15 In the present study, we did not perform intraoperative fluoroscopic localization of the osteotomy position of the ischium in all cases. The osteotomy chisel was placed close to the capsule, and the ischium was osteotomized obliquely toward the contralateral ASIS without detaching the sacrospinous ligament origin.…”
Section: Discussionmentioning
confidence: 84%
“…For the osteotomy position, it is suggested that the osteotomy should be placed as far proximally as possible on the ischial spine to minimize the effect of the rotation angle of the osteotomy site because of the limitation by the sacrospinous ligament. 15 In the present study, we did not perform intraoperative fluoroscopic localization of the osteotomy position of the ischium in all cases. The osteotomy chisel was placed close to the capsule, and the ischium was osteotomized obliquely toward the contralateral ASIS without detaching the sacrospinous ligament origin.…”
Section: Discussionmentioning
confidence: 84%
“…Joseph (1989) and Huhnstock et al (2014a, 2014b) ascertained that the affected side of children diagnosed with Legg‐Calve‐Perthes disease had higher angle values from the unaffected side; Torode and Young (2015) and Balakumar et al (2018) reported that SA significantly decreased from the preoperative to the postoperative period in those planned to undergo TPF (Transphyseal Screw Fixation) and osteotomy surgery. Abousamra et al (2016) reported that mean SA measurements of children with cerebral palsy were 53° in the preoperative period and 44° in the postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…С тех пор эта хирургическая методика получила многочисленные модификации, которые в первую очередь касаются количества доступов к костям таза [14,15,16,17]. На сегодняшний день все чаще появляются публикации об использовании малоинвазивных хирургических методов для выполнения тройной остеотомии таза [18,19,20,21].…”
Section: таблица 3 значения основных рентгенометрических параметров х...unclassified
“…Так, B. Balakumar с соавторами описывают выполнение тройной остеотомии таза из доступа типа «бикини» с длиной разреза 5-7 см, а W.B. Lehman с соавторами и вовсе выполняют данную операцию из двух «практически чрескожных» косметических доступов [18,19]. Одновременно с этим необходимо отметить, что об эффективности тройной остеотомии таза, выполненной из малоинвазивных доступов, судят лишь по степени достигнутой коррекции и протяженности разреза кожи.…”
Section: таблица 3 значения основных рентгенометрических параметров х...unclassified
See 1 more Smart Citation